2012
DOI: 10.1007/978-3-642-32796-4_15
|View full text |Cite
|
Sign up to set email alerts
|

How Does Representation Modality Affect User-Experience of Data Artifacts?

Abstract: Abstract. We present a study that explores people's affective responses when experiencing data represented through different modalities. In particular, we are interested in investigating how data representations that address haptic/tactile and sonic perception are experienced. We describe the creation of a number of data-driven artifacts that all represent the same dataset. In taking a phenomenological approach to our analysis, we used the Repertory Grid Technique (RGT) during a group session to elicit partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 15 publications
2
18
0
1
Order By: Relevance
“…Regarding the strategies that participants employed to interpret the data, our findings confirm previous research [20]: participants tried to find analogies between the readings from the data probes and familiar sounds or sensations that they had previously experienced to make sense of the data. However, the micro-phenomenological interviews indicate that participants subconciously made use of mental images to make sense of the data (e.g., translating sounds into points on a horizontal line, revealing higher and lower values), which parallels previous research on children solving math problems [39] and how people experience simple graphs and charts on a personal level [19].…”
Section: Data Interpretation and Processsupporting
confidence: 82%
See 1 more Smart Citation
“…Regarding the strategies that participants employed to interpret the data, our findings confirm previous research [20]: participants tried to find analogies between the readings from the data probes and familiar sounds or sensations that they had previously experienced to make sense of the data. However, the micro-phenomenological interviews indicate that participants subconciously made use of mental images to make sense of the data (e.g., translating sounds into points on a horizontal line, revealing higher and lower values), which parallels previous research on children solving math problems [39] and how people experience simple graphs and charts on a personal level [19].…”
Section: Data Interpretation and Processsupporting
confidence: 82%
“…[20]), not much research has compared haptic with visual and auditory representation modalities. Hogan and Hornecker [20] found that people appear to rely more on intuition and realworld experiences when making sense of haptic and sonic, compared to visual representations, and tend to engage in more personal, emotionally-driven interpretations. In contrast, a visual representation (a bar graph) was experienced more as a pragmatic tool.…”
Section: Physical Representationsmentioning
confidence: 99%
“…Intermodal Perception: The idea of conveying data to several senses has been around (e.g., [26,42,56]) but has typically followed a multimodal approach, where multiple output devices address the senses separately. In contrast, data physicalization follows an intermodal approach [64] that guarantees cohesive and realistic multisensory experiences.…”
Section: Leveraging Our Perceptual Exploration Skillsmentioning
confidence: 99%
“…For example, the benefits of the physicalizations used by Rosling (Figure 2-right) likely lie in their pedagogical and persuasive power. Other criteria relevant to physicalizations include the insights gained from interacting with them [51], the extent to which they promote engagement and behavior change, their memorability [8], and the affective responses they elicit [26]. Taking inspiration from work on visualization evaluation scenarios [37], it also seems important to explore methodologies for understanding how people reason, collaborate and communicate with physicalizations.…”
Section: Evaluation-specific Challengesmentioning
confidence: 99%
“…Observations of visitors of a space observatory indicate that this kind of representation engaged visitors, and felt more real and less abstract than purely graphical representations. In a previous study, they had found clues that the modality and modality combinations used to represent data can influence the experience [Hogan and Hornecker, 2012]. Roberts and Walker [2010] encouraged the InfoVis community to develop a unified theory that covers all human senses and allows the integration of multiple modalities.…”
Section: Examples For Physicalizationsmentioning
confidence: 99%